Предмет: Алгебра, автор: egor79881

иррациональные уравнения

Приложения:

Ответы

Автор ответа: narminmamedzadeh
1

Ответ:

 \sqrt{ {x}^{2}  + 2x + 10} = 2x - 1 \\  {x}^{2}  + 2x + 10 = 4 {x}^{2}  - 4x + 1 \\3 {x}^{2}  - 6x - 9 = 0 \\  {x}^{2}  - 2x - 3 = 0 \\ x1 =  - 1 \\ x2 = 3 \\  \\  \sqrt{2x - 1}  = 2 - x \\ 2x - 1 = 4 - 4x +  {x}^{2}  \\  {x}^{2}  - 6x + 5 = 0 \\ x1 = 1 \\ x2 = 5 \\  \\  \sqrt{3x - 2}  = 2 - x \\ 3x - 2 = 4 - 4x +  {x}^{2} \\  {x}^{2}  - 7x + 6 = 0 \\ x1 = 1 \\ x2 = 6

Похожие вопросы